(untitled) (LEARNing Landscapes, 2014)
Inclusion is a contemporary educational movement impacting the role of the classroom teacher. As a result, teacher education programs have made attempts to incorporate inclusive education as part of their curricula. An analysis of the literature reveals that inclusion training has favorable effects on the attitudes of preservice teachers, but has little effect on their perceptions of preparedness to teach in inclusive classrooms. A common complaint is that the focus is heavily weighted on theory, as opposed to practical experience. To address such concerns, the authors recommend the Individual Direct Experience Approach (IDEA) as an innovative approach to preparing teachers for inclusive classrooms.